Wages and Hours in Consumers' Cooperatives in Great Britain and the United States - Miller, Glenn W. (Quarterly Journal of Economics, 1941)
Journal Article Wages and Hours in Consumers' Cooperatives in Great Britain and the United States Get access Glenn W. Miller Glenn W. Miller Ohio State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 55, Issue 2, February 1941, Pages 294–305, https://doi.org/10.2307/1882063 Published: 01 February 1941